2016
DOI: 10.3389/fnhum.2016.00039
|View full text |Cite
|
Sign up to set email alerts
|

The Representation of Objects in Apraxia: From Action Execution to Error Awareness

Abstract: Apraxia is a well-known syndrome characterized by the sufferer’s inability to perform routine gestures. In an attempt to understand the syndrome better, various different theories have been developed and a number of classifications of different subtypes have been proposed. In this article review, we will address these theories with a specific focus on how the use of objects helps us to better understand upper limb apraxia. With this aim, we will consider transitive vs. intransitive action dissociation as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 137 publications
(192 reference statements)
1
24
0
2
Order By: Relevance
“…This object-based movement description is based on neuroscientific literature. Indeed, upper limb movements can be grouped in three broad categories according to neuro-psychological and behavioural criteria [8], [50], [51]. More in detail, these three types of movements are: (i) intransitive actions, i.e., not involving the use of any object, yet meaningful and/or communicative; (ii) transitive actions, i.e., characterised by the interaction with a single object; and (iii) tool mediated actions, i.e., indicating tasks where an object is used as a tool to interact with another one [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This object-based movement description is based on neuroscientific literature. Indeed, upper limb movements can be grouped in three broad categories according to neuro-psychological and behavioural criteria [8], [50], [51]. More in detail, these three types of movements are: (i) intransitive actions, i.e., not involving the use of any object, yet meaningful and/or communicative; (ii) transitive actions, i.e., characterised by the interaction with a single object; and (iii) tool mediated actions, i.e., indicating tasks where an object is used as a tool to interact with another one [1].…”
Section: Introductionmentioning
confidence: 99%
“…More in detail, these three types of movements are: (i) intransitive actions, i.e., not involving the use of any object, yet meaningful and/or communicative; (ii) transitive actions, i.e., characterised by the interaction with a single object; and (iii) tool mediated actions, i.e., indicating tasks where an object is used as a tool to interact with another one [1]. These classes of action have already been extensively described in terms of psychological and behavioural response in several medical studies focused on apraxia [8], [50], [51], i.e., the inability to perform purposive actions as a result of a brain damage. Moreover, the topographical representation of the associated neural activity has been already studied using fMRI [52].…”
Section: Introductionmentioning
confidence: 99%
“…Apraxia, a disorder of complex movement, is one example where this can be the case. Patients with apraxia can show deficits in, among other skills, the ability to imitate meaningful or meaningless actions (Buxbaum & Kalénine, 2010;Buxbaum & Randerath, 2018;Canzano et al, 2016;Petreska et al, 2007;Rumiati et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In the task space, it is possible to identify three main classes of actions associated with different neuropsychological correlates [8], [25], [26]: intransitive (i.e., meaningful gestures that do not include the use of objects), transitive (i.e., actions involving an object), and toolmediated (i.e., actions in which an object is used to act upon another) [2]. A functional imaging study [27] has already demonstrated that these three classes of actions generate distinct neural patterns in the human brain during motor visualisation, and exhibit a specific topographical organisation of the brain response.…”
Section: Introductionmentioning
confidence: 99%